qPCR in a suitcase for rapid Plasmodium falciparum and Plasmodium vivax surveillance in Ethiopia - Lise Carlier; Sarah Cate Baker; Tiffany Huwe; Delenasaw Yewhalaw; Werissaw Haileselassie; Cristian Koepfli (Public Library of Science (PLoS), 2022)
Many Plasmodium spp. infections, both in clinical and asymptomatic patients, are below the limit of detection of light microscopy or rapid diagnostic test (RDT). Molecular diagnosis by qPCR can be valuable for surveillance, but is often hampered by absence of laboratory capacity in endemic countries. To overcome this limitation, we optimized and tested a mobile qPCR laboratory for molecular diagnosis in Ziway, Ethiopia, where transmission intensity is low. Protocols were optimized to achieve high throughput and minimize costs and weight for easy transport. 899 samples from febrile patients and 1021 samples from asymptomatic individuals were screened by local microscopy, RDT, and qPCR within a period of six weeks. 34/52 clinical Plasmodium falciparum infections were missed by microscopy and RDT. Only 4 asymptomatic infections were detected. No hrp2 deletions were observed among 25 samples typed, but 19/24 samples carried hrp3 deletions. The majority (25/41) of Plasmodium vivax infections (1371 samples screened) were found among asymptomatic individuals. All asymptomatic P. vivax infections were negative by microscopy and RDT. In conclusion, the mobile laboratory described here can identify hidden parasite reservoirs within a short period of time, and thus inform malaria control activities.